Antanas Baranauskas akcentologas - Stundžia, Bonifacas (Baltistica, 1989)
ANTANAS BARANAUSKAS AS ACCENTOLOGISTOn the basis of preliminary accentological analysis of Baranauskas’s texts which represent the accentuation of his native Eastern Aukštaičiai dialect of the Anykščiai District it has been concluded that (1) although the distinctions between syllable intonations of monophthongs in Baranauskas’s times seem to have not been very prominent already, he, due to his good linguistic ear, distinguished them fairly well; (2) in some cases the syllable intonation is determined not only by ear but also on the basis of analogy with the respective full forms; (3) in Baranauskas’s times there were still no accent retraction in his native dialect, although some rudiments of it already existed; (4) the facts of Baranauskas’s accentuation can be used more reliably than has been thought up till now and his texts can be considered an important source for investigating the system and development of Eastern Lithuanian accentuation.